Graphene-supported ZnO nanoparticles: An efficient heterogeneous catalyst for the Claisen-Schmidt condensation reaction without additional base. Issue 42 (18th October 2017) - Li, Zhuofei; Zhao, Hongyan; Han, Huatao; Liu, Yang; Song, Jinyi; Guo, Weihao; Chu, Wenyi; Sun, Zhizhong
Graphical abstract: Highlights: ZnO nanoparticles supported on reduced graphene oxide were prepared. ZnO/RGO as catalyst was applied to the Claisen-Schmidt condensation. A new catalytic system was developed under microwave conditions. ZnO/RGO could be recycled without obvious losses of catalytic activity. Abstract: ZnO nanoparticles supported on reduced graphene oxide (ZnO/RGO) were prepared by the hydrothermal method and characterized by TEM, XPS, XRD, and Raman spectroscopy. As a green catalyst, ZnO/RGO was applied to the Claisen-Schmidt condensation reaction of aryl aldehydes and aryl ketones under microwave irradiation. Therein, chalcone products could be efficiently synthesized and easily separated from the heterogeneous catalysis system. The catalyst could be recycled four times without significant loss of catalytic activity.